Penerapan Pembelajaran Berbasis Proyek dengan E-Learning untuk Meningkatkan Kreativitas dan Hasil Belajar Mahasiswa pada Mata Kuliah IPA Terpadu - Indica Yona Okyranida (Navigation Physics : Journal of Physics Education, 2020)
In this study aims to determine the influence of implementation of project-based learning with e-learning to improve creativity and student learning outcomes in the integrated SCIENCE course. The results of creativity data obtained from the poll of creativity given to the students get the pretests results got the lowest score of 45 and the posttest can be the lowest score of 68, so it can be concluded there is a score increase on the lowest score. At the highest score when the pretests obtained the results 68 and posttest 80 and concluded there is a rise in the highest score. Average pretests results obtained 58 and Posttest 75, so learning using the project has a significant influence on student creativity. Results of cognitive learning results derived from the test problem given to students getting pretests results get the lowest score of 55 and on the posttest can be the lowest score of 70, so that there can be a score increase on the lowest score. At the highest score when the pretests obtained the results 75 and Posttest 87 and concluded there is a rise in the highest score. Average pretests results obtained 63 and Posttest 79, so that learning using the project has a significant influence on student learning outcomes.